Death by bikini - Gerber, Linda C. (New York : Sleuth/Speak, 2008)
Sixteen-year-old Aphra Behn Connolly investigates why her father let an unknown family stay at their exclusive tropical island resort, who strangled a famous rock star's girlfriend with her own bikini top, and what a smoldering teenaged guest is hiding
Keywords: Resorts -- Fiction; Murder -- Fiction; Fathers and daughters -- fiction; Islands -- Fiction; Mystery and detective stories